Perancangan aplikasi sistem manajemen kelola pendataan dan penjualan salon kecantikan (Lia Salon) berbasis web - Tato, Karolina; Yasin, Verdi; Sianipar, Anton Zulkarnain; Ichwan, Hidayatul (Journal of Engineering, Technology and Computing (JETCom), 2025)
Beauty salon (Lia Salon) is a form of business or a special place for women to beautify and beautify the body which provides care services related to skin health, cosmetic care, face, hair, nails and so on, and also sells beauty products such as facial wash, hand body soap and other beauty needs. The price offered is relatively cheap with good quality, making more and more customers. So that it requires a beauty salon governance management application to overcome problems that occur in services and transactions in the sales and registration system quickly, precisely and accurately. The problem with beauty salons (lia salons) is that the management of data collection and sales still uses a manual system by recording them in a book, which makes data difficult to find and easy to lose. The method used to build the system is using the Waterfall method and system modeling using the Unified Modeling Language (UML). The results of this study are in the form of web-based applications that can help beauty salons to more easily collect consumer data, sales transactions and financial reports.